POWER SUPPLY INVERTER DC-DC SEBAGAI SUPPLY AUDIO AMPLIFIER - Wardani, Ilham Setiya; Manan, Saiful (Gema Teknologi, 2016)
Ilham Setiya Wardani, Saiful Manan in this paper explain that Utilization of power electronics components in the process of conversion of electrical energy has been growing from year to year. for controlling power from one form to another is very important and the characteristics of the equipment of power electronics has allowed it. DC-DC converters can also be called a wave DC inverter capable of producing symmetrical widely used and applied in industry and everyday life.In the inverter power supply are made using half-bridge converter topology. Half-bridge converter topology has several advantages that are easy to create and output a lot easier in the controlling. The process of switching at the half bridge converter using mosfet IRFZ44N and executed using ICTL494.In the design of the tool, using the supply is 12 Volt DC that directly goes to IC TL494 and frequency output that is generated directly toward the driver mosfet with the type BC327 used to mesaklarkan mosfet by means of on / off alternately to supply the power transformer intiferit to raise the voltage to 26 volt AC that will be rectified by using fast diode recofery MUR1560 to rectify the AC into DC voltage with the output voltage of +/- 26 volts DC.Â Keywords: power supply, inverter, TL494ReferencesBarkhordarian, V. Power MOSFET Basics. International Rectifier: California. E-book :www.aosmd.com. Didownload pada april 2016. Pukul 21.15 WIB.Hermawan, H. Rancang Bangun Sistem Kendali High Frequency Induction Heating. Skripsi S1 Teknik Elektro. Jakarta: Universitas Indonesia.Malvino . 1995. Prinsip-prinsip Elektronika. Jakarta : Erlangga.Maruitula, Edison. 2011. Rancang Bangun Flyaback Regulator Untuk Mencatu Sistem Pensaklaran IGBT pada Invereter. Skripsi S1 Teknik Elektro .Depok : Unversitas Indonesia.Muis, Saludin. 2013. Perancangan Teori Dan Praktis Power Supply Jenis Switch Mode. Yogyakarta : Graha Ilmu.Rasyid, Muhammad H. 1999. Elektronika Daya. Jakarta : PT Prenhallindo.